Effects of high levels of phytase (Ronozyme HiPhos) in low-lysine diets on the growth performance of nursery pigs - Kari Beth Langbein; Robert D Goodband; Michael D Tokach; Steven S Dritz; Joel M DeRouchey; J R Bergstrom (Kansas Agricultural Experiment Station Research Reports, 2013)
Two studies were conducted to determine the effects of added phytase in nursery pig diets formulated at or below their dietary lysine requirements. In Exp. 1, a total of 360 nursery pigs (PIC 327 × 1050, initially 27.3 lb) were used in an 18-d study with 5 pigs per pen and 18 pens per treatment in a university research facility. Pens of pigs were randomly allotted to 1 of 4 dietary treatments arranged in a 2 × 2 factorial with main effects of lysine level (adequate; 1.2% standardized ileal digestible [SID] lysine vs. marginal; 1.05% SID lysine) and phytase level (500 vs. 3,000 phytase units [FTU]/kg) with Ronozyme HiPhos (DSM Nutritional Products, Parsippany, NJ) as the source of phytase. Overall (d 0 to 18), no (P>0.37) lysine × phytase interactions and no differences (P>0.14) were observed among phytase levels. Pigs fed adequate lysine diets had greater (P<0.01) ADG and BW and better F/G than those fed marginal lysine diets. In Exp. 2, 2,592 nursery pigs (PIC 1050 × 337, initially 23 lb) were fed 1 of 6 dietary treatments over 2 phases in a 36-d study in a commercial research barn. Dietary treatments included an adequate lysine (1.20 and 1.10% SID lysine in Phases 1 and 2, respectively) positive control diet containing 250 FTU/kg of phytase, or 5 low-lysine (1.10 and 1.00% SID lysine in Phases 1 and 2, respectively) diets with 250, 500, 1,000, 2,000, or 3,000 FTU/kg of phytase. Overall, pigs fed the positive control had greater (P<0.02) ADG and better F/G than pigs fed the low-lysine diet with the same amount of phytase. Increasing phytase in the low-lysine diets increased (quadratic, P<0.02) ADG, with the optimum response observed in pigs fed 1,000 FTU/kg. Phytase did not affect F/G. In summary, these studies confirmed the importance of feeding adequate lysine to optimize gain and feed efficiency. These studies also illustrate the differences between studies conducted in university vs. commercial settings because only the commercial study yielded a detectable phytase response. In the commercial study, pigs fed the low-lysine diet with 1,000 FTU/kg of phytase had performance similar to pigs fed high-lysine diets containing 250 FTU/kg of phytase.; Swine Day, Manhattan, KS, November 21, 2013
Keywords: Swine day; 2013; Kansas Agricultural Experiment Station contribution; no. 14-044-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1092; Phosphorous; Phytase; Nursery pig